Individual Characteristics predisposing undergraduate students to Suicide Ideation in the University of Cape Coast, Ghana. - Adom-Mensah, Benedicta Ama (Journal of Advanced Psychology, 2022)
Purpose: The purpose of the study was to find out the individual characteristics predisposing undergraduate students to suicide ideation in the University of Cape Coast. Methodology: A mixed methods approach was used in which a quasi-experimental research design, specifically, the pre-test, post-test and control group design was combined with a qualitative phase. A total of 30 undergraduate students from four colleges of the University of Cape Coast in the Central Region of Ghana were non- randomly assigned to two treatment groups Individual Psychology and Cognitive Behavioural Therapy (IP and CBT) and one control group. Beck Scale for Suicide Ideation was used for the collection of data for the study. To assess the individual characteristics that predispose undergraduate students of UCC, Chi square test for association was employed as an appropriate tool for the analysis. Findings: The study revealed that age, gender, program of study and level of study of the students have significant association with students who are predisposed to suicide ideation. Unique Contribution to Theory, Policy and Practice: It was recommended that constant screening of suicide ideation be done as part of the University's program to be organised by the Counselling Center. This is to help educate and create more awareness on suicide ideation and bring in more people per the screening to benefit from counselling therapies which in turn will help reduce suicide ideation on our campus.